2017
DOI: 10.1007/s10695-017-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in gene expression and physiological response in red drum Sciaenops ocellatus exposed to a long-term freshwater environment

Abstract: Red drum (Sciaenops ocellatus) is a euryhaline fish commonly found in the Gulf of Mexico and along the Atlantic coast of North America. Because of high commercial demand and its euryhaline characteristics, aquaculture of this species has diversified from marine to low-salinity aquaculture systems. In recent years, interest in the feasibility of producing red drum in inland freshwater systems has grown and this prompted us to investigate its osmoregulatory capacity after rearing for 8 months in a freshwater aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The growth of juveniles has been reported for salinity conditions of 11 ppt in RAS growout tanks (Pfeiffer & Wills, ). Similarly, it has been reported that acclimated red drum cultivated for long periods have undergone phenotypic plasticity and physiological changes at a salinity of 0 ppt (Gullian‐Klanian, ; Gullian‐Klanian, Zapata‐Pérez, & Vela‐Magaña, ). Therefore, the aim of this article is to present biological and technological indicators of an inland culture of S. ocellatus in a freshwater semirecirculation system, without the addition of ions or chemical elements for a long‐term culture period.…”
Section: Introductionmentioning
confidence: 82%
“…The growth of juveniles has been reported for salinity conditions of 11 ppt in RAS growout tanks (Pfeiffer & Wills, ). Similarly, it has been reported that acclimated red drum cultivated for long periods have undergone phenotypic plasticity and physiological changes at a salinity of 0 ppt (Gullian‐Klanian, ; Gullian‐Klanian, Zapata‐Pérez, & Vela‐Magaña, ). Therefore, the aim of this article is to present biological and technological indicators of an inland culture of S. ocellatus in a freshwater semirecirculation system, without the addition of ions or chemical elements for a long‐term culture period.…”
Section: Introductionmentioning
confidence: 82%
“…Our observations between species were reasonable in contrast to the transcriptomic variation of populations within Crassostrea virginica , where two reef‐source populations showed a greater environment effect than genetic effect on gene expression differences in response to different salinity environments (Eierman & Hare, 2016). Furthermore, transporters (especially SLCs), taurine metabolism pathway, and pyruvate metabolism pathway enriched in the salinity‐correlated module were in response to salinity gradients, which were supported by those of previous studies (SLCs: Boyle et al, 2015; Choi et al, 2003; Hoglund et al, 2011; Hui et al, 2014; Jiang et al, 2020; Kurita et al, 2008; Li et al, 2021; Menchini & Chaudhry, 2019; Nakajima et al, 2013; Wang et al, 2015; Wang et al, 2020; Wu et al, 2021; Zhou et al, 2018; Taurine: Meng et al, 2013; Wu et al, 2021; Pyruvate: Derakhshani et al, 2020; Gullian et al, 2018; Wang, Li, et al, 2017). These salinity‐responsive pathways also exhibited divergent responses between two oyster species for their enrichment of DEG sets for the species effect and in species‐correlated modules, emphasizing the role of these mechanisms in the formation of divergence in salinity adaptation between the two species.…”
Section: Discussionmentioning
confidence: 99%